2005
DOI: 10.1111/j.0105-1873.2005.00565.x
|View full text |Cite
|
Sign up to set email alerts
|

Patch testing with a new fragrance mix detects additional patients sensitive to perfumes and missed by the current fragrance mix

Abstract: The currently used 8% fragrance mix (FM I) does not identify all patients with a positive history of adverse reactions to fragrances. A new FM II with 6 frequently used chemicals was evaluated in 1701 consecutive patients patch tested in 6 dermatological centres in Europe. FM II was tested in 3 concentrations - 28% FM II contained 5% hydroxyisohexyl 3-cyclohexene carboxaldehyde (Lyral), 2% citral, 5% farnesol, 5% coumarin, 1% citronellol and 10%alpha-hexyl-cinnamic aldehyde; in 14% FM II, the single constituen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
122
2
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(136 citation statements)
references
References 18 publications
7
122
2
5
Order By: Relevance
“…In fact, to our knowledge, no previous studies have investigated the prevalence of fragrance mix 2 sensitization in the general population. The frequency of contact sensitization to fragrances strictly depends on the number of allergens tested, and patch testing with fragrance mix 2 detects additional patients sensitive to perfumes and missed by fragrance mix 1 testing [7,12,13]; thus, we would expect that the overall prevalence of contact sensitization to fragrances would be higher than prevalence estimates so far. This inclusion could account, at least in part, for the relatively high frequency of contact sensitization to fragrances we found in the pilot investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, to our knowledge, no previous studies have investigated the prevalence of fragrance mix 2 sensitization in the general population. The frequency of contact sensitization to fragrances strictly depends on the number of allergens tested, and patch testing with fragrance mix 2 detects additional patients sensitive to perfumes and missed by fragrance mix 1 testing [7,12,13]; thus, we would expect that the overall prevalence of contact sensitization to fragrances would be higher than prevalence estimates so far. This inclusion could account, at least in part, for the relatively high frequency of contact sensitization to fragrances we found in the pilot investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Para estudiar esta reactividad anual y evolutiva seleccionamos 3 alérgenos; níquel, mezcla de fragancias (por ser los más importantes en mujeres y hombres respectivamente) y p-fenilenediamina, porque su inclusión en la batería estándar ha sido materia de amplia discusión recientemente 20,21 .…”
Section: Mezcla De Fragancias 14unclassified
“…Esto podría explicarse por recientes sustituciones de algunos alérgenos en las nuevas formulaciones cosméticas. Lo anterior también confirma la necesidad de incorporar una nueva batería de alérgenos para fragancias (MF II) a nuestras baterías estándar, como se ha hecho en otros lugares del mundo 20,21 . figura 3.…”
Section: Mezcla De Fragancias 14unclassified
“…1 Studies performed in Europe and in the United States have clearly demonstrated that adding lyral or fragrance mix II to patch test panels used for patients with suspected fragrance allergy will identify some individuals with fragrance allergy who are not diagnosed with the standard fragrance allergens. 2,3 The European study found that 4% of patients reacted to fragrance mix II and that nearly half of these patients did not react to the standard fragrance mix. 2 The US study found that 0.4% of patients reacted to lyral.…”
mentioning
confidence: 99%